EVALUASI PREDIKSI UMUR SISA PERKERASAN LENTUR METODE PEDOMAN 2005, AASHTO 1993, DAN BACKCALCULATION - Aloysius Tjan (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
Structural flexible pavement evaluation can be performed by measuring vertical deflection on the pavement surface. FWD (Falling Weight Deflectometer) is one of the available apparatus for this purpose. There are several different methods to analyze the deflections such as backcalculation, AASHTO 1993, and Pedoman 2005. Remaining life of the existing pavement on Pedoman 2005 based on solely the deflection at the center of the loading plated at standard pavement temperature (35oC), standard loading (4.08 tons), and depends on water ground level – without evaluating structural layers moduli. On the other hand, AASHTO method based on a deflection relatively far from the center, and a deflection at the center of the loading plate at standard pavement temperature (68oF). The AASHTO evaluates resilient modulus of subgrade, and effective modulus of pavement structure above the subgrade – and later the pavement remaining life. Other than the previous methods, output of backcalculation method are every and each pavement layers moduli that has been modelled. The remaining life is determined by using AASHTO relationship number of load repetitions and effective structural number. As the results of MICHBACK subgrade resilient modulus is greater (114.6%) than the AASHTO. Effective structural number of MICHBACK is less (92.32%) than the AASHTO. The combined differences on subgrade resilient modulus dan effective structural number on remaining life of the MICHBACK is 70.6% of the AASHTO. While remaining life of Pedoman 2005 is 125.8% of MICHBACK. When results of MICHBACK backcalculation is considered as referenced, calibration factor for remaining life of AASHTO is 0.706, and Pedoman is 0.78